REGIONAL PRIVILEGES OF THE GRAND DUTCHY OF LITHUANIA AS THE CONSTITUTIONAL ACTS OF LITHUANIA - Machovenko, Jevgenij; Griškevič, Lina (Teisė, 2015)
Using legal instruments authors of the article aim to determine whether the regional privileges of the Grand Dutchy of Lithuania (hereinafter referred to as GDL) of 1387-1568 can be refereed to normative legal act or normative legal contract – one of the recognized source of law. There should be also revealed the special procedure of lawmaking and external result expression, which let to ascribe the privileges to the constitutional law (not ordinary law) sources. Finally, the formal legal connection between the privileges and later constitutional acts of GDL – three Lithuanian Statutes and integrated Constitution of 1791, is revealed.Firstly, the preconditions and necessity to emerge, resources for issue of the regional privileges of GDL are explored While analyzing the situation of state formation of those days, the authors conclude that there were preconditions for emergence of regional norms as well as the external form for norms – normative legal act, at the end of XIV century. The regional normative legal acts of GDL naturally originated as privileges – the type of normative legal act that is typical to medieval European law.In the second part of the article the process of issuing, recording and systematization of the regional privileges of GDL are analyzed and they are characterized as the result of lawmaking.The part of lawmaking raised to the level of regional privileges regulated four types of public relations, which fell within the public law sphere and most of it – within the constitutional sphere (in the light of modern jurisprudence). The specific of process of issuing, recording and systematization (which was a rare phenomena in GDL) of the regional privileges of GDL distinguished them as having higher legal power comparing to other normative legal acts and other sources of law.The scientific explanation for the validity of these privileges is given in the third part of the article. The authors state that the connection between the privileges and three Lithuanian Statutes may be explained in the light of interaction among the Act of February 16, 1918, the Resolution of constituent Seimas of May 15, 1920 and later constitutional acts. It is inferred, that from the formal legal point of view all the regional privileges in GDL issued in 1387–1568 were the sources of constitutional law (constitutional legal acts) in the modern sense of the term.